Content-based image retrieval using a signature graph and a self-organizing map - Van, Thanh The; Le, Thanh Manh (Zielona Góra: Uniwersytet Zielonogórski)
In order to effectively retrieve a large database of images, a method of creating an image retrieval system CBIR (content-based image retrieval) is applied based on a binary index which aims to describe features of an image object of interest. This index is called the binary signature and builds input data for the problem of matching similar images. To extract the object of interest, we propose an image segmentation method on the basis of low-level visual features including the color and texture of the image.
Keywords: binary signature; similarity measures; signature graph; image retrieval